An organized start to implant-supported prosthesis - Suma Karthigeyan; Seyed Ashraff Ali; Kalarani Mohan; Mangala Deivanai (Wolters Kluwer Medknow Publications, 2013)
Various treatment options are available for rehabilitating the complete edentulous patients with implants. However, due consideration for the prosthesis is not given prior to implant surgery. This can result in implant being placed in locations that do not provide the best esthetic and functional result. Incorrect implant localization and angle are the primary cause of non-axial loading and may contribute to loss of Osseo-integration. For predictable outcome, the treatment should begin with visualizing the end result. A step-wise pre-implant surgery evaluation is necessary to achieve the objectives. This is a case report of a completely edentulous patient who was treated with fixed implant prosthesis following various steps in the pre-implant surgery evaluation.